Use of cryopreserved whole blood samples in the Comet assay for detection of DNA damage in human population studies - K.L. Cooper; E.J. Dashner-Titus; J. Ong; D. MacKenzie; L.G. Hudson (MethodsX)
Many human population studies rely on blood samples to test for DNA damage as a biomarker of occupational or environmental exposures, nutrition, disease states or other health concerns. Often sample collection occurs outside of clinical settings in locations lacking immediate access to appropriate technical equipment. We describe a method for the collection of whole blood using dimethyl sulfoxide stabilization followed by cryopreservation that is suitable for samples collected in settings with minimal laboratory equipment. The impact of parameters such as temperature and time of cryopreservation on DNA damage was determined as measured by the comet assay. This method will assist researchers in defining conditions post-phlebotomy to maintain DNA integrity before analysis of DNA damage. We provide evidence that a limited number of freeze thaw cycles are feasible which allows for secondary analysis of samples. Proof of concept is further illustrated through samples collected in remote locations. • Freshly drawn whole blood is aliquoted into DMSO containing cryotubes with slow freeze followed by long term storage in liquid nitrogen which allows repeat sample analysis (1-2 freeze/thaw cycles). • Use of internal quality assurance samples ensures the reliability of DNA damage findings when analysis is conducted at different times over the course of an extended study.